The Vitamin D Binding Protein Gene Polymorphism Association with Covid-19-Infected Iraqi Patients: Association of Vitamin D Binding Protein with COVID-19 - Abdulameer, Nawres Adnan; Eleroui, Malek; Nasser, Hassan H.; Amara, Ibtissem Ben (Cellular and Molecular Biology, 2023)
Vitamin D deficiency, in general, is usually correlated with increased risks of chronic pulmonary disease such as COVID-19 infection. However, the mechanisms are still unknown. Herein, this study aimed to investigate the correlation between vitamin D binding protein gene polymorphism and COVID-19-infected Iraqi patients. The study has been conducted on patients with Covid-19 during the period extended from June, 2021 to April, 2022. 300 samples were collected from healthy and infected people. The demographic characteristics of patients (age, gender and residency) are shown non-significant in all. However, the distribution of DBP (rs12785878-T/G) Polymorphism was detected by Allele Specific PCR technique. The association between DBP (rs12785878) gene polymorphism and risk of Covid-19 is also shown, the heterozygous genotype TG was more frequent in the patients’ group in comparison with the control group, 66 versus 58, respectively. Therefore, genotype TG was a genetic risk factor for Covid-19 with an odds ratio of 2.4074 (95% confidence interval of 1.2462-4.6505) and an etiologic fraction of 0.2963. In the addition, the homozygous genotype GG was more frequent in the patients’ group in comparison with the control group, 65 versus 54, respectively, Therefore, genotype GG was a risk factor for Covid-19 with an odds ratio of 1.0578 (95% confidence interval of 0.6386-1.7522) and an etiologic fraction of 0.0299. thus, it can be seen that Covid-19 disease has a direct effect on the level of vitamin D in patients infected with the virus compared to healthy people.